Level of influence of AM Radio commentary programs on listeners' political view. - Demegillo, Freya Danacris; Gayatgay, Mae Belle; Grajales, Susie; Laboro, Felisa
Radio has been a significant medium in expressing different point of views. It is also considered as a powerful tool in shaping the political awareness and conception of the people. The emergence of commentary programs in AM radio stations has become very influential on the listeners especially to those who were not well informed about the issues aside from what they've heard., Despite the emergence of modern sources of information, radio is still effective in playing significant roles. Aside from providing news and entertainment, radio has influenced the audience's ideas and opinions through commentary programs. in terms of awareness, they do not just become familiar of the different societal issues especially the political ones but they are given the chance to analyze these things. They become politically aware of the different motives and intentions of politicians by exposing themselves to the commentaries. In these commentary programs, various angles of issues are tackled, prominent individuals are introduced, and different opinions and ideas are being raised. The study conducted has proven that until now, people rely on the power of radio in providing them with the information that they are looking for. What the people hear over these commentary programs becomes their basis in judging the different issues that bombard them. Having the awareness, they could protect themselves from being carried away by the issues. Since there are different political issues that the people face today, they get confused of which of these issues are they going to believe in. With the help of the commentary programs the audience is able to identify issues that could influence them in a good way or harm them.